Total and Unilateral Peak Nasal Inspiratory Flow and Unilateral Visual Analogue Scale: Rationale in Indication and Outcomes of Septoplasty?. Issue 7 (October 2019) - Schalek, Petr; Guha, Anasuya; Ondrová, Tereza; Svoboda, Milan
Abstract : Abstract: Septoplasty is one of the most frequently performed procedures in otorhinolaryngology. Proper selection of patients for septoplasty as well as examination is essential for good outcome of surgery. The aim of this study was to evaluate the suitability of combination of 2 simple, cheap, and easily performed examinations for indication and outcomes of septoplasty to evaluate the effectiveness in this type of surgery. Seventy patients were enrolled from 2 tertiary centers from the period of April 2017 to March 2018, who all underwent septoplasty for nasal septal deviation. Total and unilateral peak nasal inspiratory flow (PNIF), unilateral visual analogue scale, and nasal endoscopy for indication and outcomes of septoplasty were performed. Furthermore, assessment of possible correlation between subjective and objective data before and 3 months after septoplasty was done. Statistical analysis was carried out on the obtained data. Postoperatively the total and both unilateral PNIF measurements increased significantly compared with corresponding preoperative values and similarly means of visual analogue scale scores on both sides decreased 3 months after the procedure. No significant correlation was seen between objective and subjective outcomes neither before the surgery, nor postoperatively. The study confirmed the suitability of using PNIF as a simple and inexpensive tool that can be a reasonable alternative to rhinomanometry and which is able to reflect changes after septoplasty. Simultaneously, along with the expected improvement in the total PNIF and unilateral PNIF on deviated side, a slight but significant improvement in PNIF values on the nondeviated side was also demonstrated.